A importância da contação de histórias na sala de aula: uma proposta de incentivo ao desenvolvimento da oralidade - Lima, Andrea Bernardes de (2015)
This work presents the results of an investigation that aimed to describe the development process of the students’ orality in schools’ environment, using the oral storytelling tradition. This research has an applied and interventionist nature, with this we promote the use of our students as an instrument in order to act as more competent transmitters of traditional oral texts based on a suggestion of education that considers the situational context of the short story genre in the oral tradition and their cultural characteristics. The term orality refers to acquired skills in spoken language as social practices. Included in this context, the school has the responsibility to teach skills directed to public presentations, developing models of communicative adaptation in which there are the “me” and the “another” interacting with each other. The storytelling plays a decisive role in the literary literacy in the classroom, providing pleasure to tell and hear stories, rescuing some of the art tradition of the ancient storytellers in oral cultures.We believe that with the huge repertory of stories, including short stories, myths and legends, the teachers may, with due authority, turn the lessons into moments of pleasure. Given these considerations, theoretically, this research is based primarily on considerations of Cascudo (1984), Benjamin (1987) and Arendt (2013). The intervention carried out in the classroom, in the other hand, is based on the proposal of didactic sequence presented by Dolz and Schneuwly (2004). This work has as a corpus 09 (nine) story telling performed by students of a public school. After the intervention process was accomplished, it was possible to notice that the difficulties previously detected in the first storytelling were properly overcome in the development of students’ orality.